Key Factors Stimulating Health Intrapreneurship in Saudi Public Hospitals - Raouf JAZIRI; Saleh ALNAHDI (Communications of International Proceedings, 2022)
Intrapreneurship is a strategic phenomenon affecting both individuals and organizations. It moves also from private to public sectors. Thus, there is many environment stimulants and constraints influencing intrapreneurial behavior within public sector bodies. This exploratory study aims to identify perceived factors by Saudi civil servants to stimulate intrapreneurship within public health sector. It investigates whether factors considered as stimulating corporate entrepreneurship in the private sector are applied to the Saudi public health sector. To do so, a questionnaire was designed and administrated to 228 public civil servants in health sector across 15 Saudi public hospitals. Results are based on Exploratory Factor analysis (EFA) and Multiple Regression analysis (MRA). Findings afford strong evidence that intrapreneurial civil servants’ penchants stimulate an intrapreneurial framework in Saudi public health sector. Two main factors stimulating intrapreneurial behavior in Saudi hospitals are found: Financial incentive and Job-rotation incentive. The study has various practical implications for both academics, decision makers and strategists concerned with boosting public health intrapreneurship.
Keywords: corporate entrepreneurship; public sector; Health sector; Saudi Arabia